2021
DOI: 10.1007/s00167-021-06545-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultracongruent insert design is a safe alternative to posterior cruciate-substituting total knee arthroplasty: 5-year results of a randomized controlled trial

Abstract: Purpose If substitution of the posterior cruciate ligament in total knee arthroplasty is necessary, there are two options available: posterior stabilized (PS) design with a post-cam mechanism or anterior-lipped ultracongruent (UC) inserts. UC inserts have the advantage that no femoral box is necessary and a standard femoral component can be used. The aim of this study was to compare the range of motion (ROM) and patient-reported outcome (PRO) after UC and PS fixed-bearing TKA. Better ROM in PS TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Previous studies have analysed knee kinematics with a navigation system, and showed less posterior tibial translation between 60° and 120° of flexion of the PS knees compared to the UC knees [4, 5, 8, 14, 17]. Despite the different kinematics, there were similar outcomes in the KSS, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Forgotten Joint scores between PS and UC groups [13, 18]. In our study, the regular use of a patellar component could have prevented possible anterior knee pain in cases with increased posterior tibial translation.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have analysed knee kinematics with a navigation system, and showed less posterior tibial translation between 60° and 120° of flexion of the PS knees compared to the UC knees [4, 5, 8, 14, 17]. Despite the different kinematics, there were similar outcomes in the KSS, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Forgotten Joint scores between PS and UC groups [13, 18]. In our study, the regular use of a patellar component could have prevented possible anterior knee pain in cases with increased posterior tibial translation.…”
Section: Discussionmentioning
confidence: 98%
“…Both groups demonstrated equally good knee function, quality of life, and high satisfaction. Patellofemoral problems were more frequent in the PS group ( P = 0.025) [ 17 ]. In a report of the results from a large national registry, Dalton found that survivorship was better for a UC device versus a PS device: the cumulative revision at 18 years was 8.3% for UC, 9.2% for CR, and 8.9% for PS [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, CS TKA features a deep dished polyethylene insert which has been proposed to lead to impingement of the femur on the posterior lip causing a subsequent reduction in flexion [18]. Several studies have examined ROM in CS designed TKA reporting variable results, but have not controlled for tibial slope or PCOR [18][19][20][21][22][23][24][25][26][27]. Both of these factors have been reported to influence flexion range at least in PS designed TKA [28].…”
Section: Discussionmentioning
confidence: 99%